2013
DOI: 10.1016/j.neuroimage.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Toward reliable characterization of functional homogeneity in the human brain: Preprocessing, scan duration, imaging resolution and computational space

Abstract: While researchers have extensively characterized functional connectivity between brain regions, the characterization of functional homogeneity within a region of the brain connectome is in early stages of development. Several functional homogeneity measures were proposed previously, among which regional homogeneity (ReHo) was most widely used as a measure to characterize functional homogeneity of resting state fMRI (R-fMRI) signals within a small region (Zang et al., 2004). Despite a burgeoning literature on R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
456
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(471 citation statements)
references
References 115 publications
(152 reference statements)
11
456
2
2
Order By: Relevance
“…Further in a voxel-wise fashion, similar to the significance test of ICC, we compared ICC values between two imaging contrasts using Z test as the following Zuo et al, 2013).…”
Section: Test-retest Reliability Quantified By Intra-class Correlationmentioning
confidence: 99%
“…Further in a voxel-wise fashion, similar to the significance test of ICC, we compared ICC values between two imaging contrasts using Z test as the following Zuo et al, 2013).…”
Section: Test-retest Reliability Quantified By Intra-class Correlationmentioning
confidence: 99%
“…ReHo is based on a data-driven approach and thus requires no prior knowledge and has good test-retest reliability [17]. It was originally proposed for measuring the degree of regional synchronization of functional magnetic resonance imaging (fMRI) time courses and focused on the similarities or coherence of the intraregional spontaneous lowfrequency (,0.08 Hz) BOLD signal, which enables a novel perspective to understand the functional regulation in particular brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that test-retest reliability of ReHo measurements increases with scan duration [18,22]. We could expect a moderate to high test retest (mean ICC=0.8) after 10minutes RS-fMRI [18], while 50 minutes scans may be required to ensure an ICC greater than 0.7 for all voxels [22].…”
Section: Evaluation Of Regional Homogeneity Processing Options On Tesmentioning
confidence: 94%
“…Brain MRI phenotypes represent ideal candidate endophenotypes for mental health disorders, as they do not rely on self-report [16] and are more and more reliably measured thanks to methodological and technological improvement [18][19][20][21][22][23][24][25]. In addition, the heritability of many MRI brain phenotypes has been established: from structural [26][27][28][29][30], to resting state and task fMRI [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%